Modeling of antibody responses to COVID-19 vaccination in patients with rheumatoid arthritis - Yun Kyu Kim; Yunhee Choi; Ji In Jung; Ju Yeon Kim; Mi Hyeon Kim; Jeffrey Curtis; Eun Bong Lee (Scientific Reports, 2024)
Abstract To construct a model of the antibody response to COVID-19 vaccination in patients with rheumatoid arthritis (RA), and to identify clinical factors affecting the antibody response. A total of 779 serum samples were obtained from 550 COVID-19-naïve RA patients who were vaccinated against COVID-19. Antibody titers for the receptor binding domain (anti-RBD) and nucleocapsid (anti-N) were measured. The time from vaccination, and the log-transformed anti-RBD titer, were modeled using a fractional polynomial method. Clinical factors affecting antibody responses were analyzed by a regression model using generalized estimating equation. The anti-RBD titer peaked at about 2 weeks post-vaccination and decreased exponentially to 36.5% of the peak value after 2 months. Compared with the first vaccination, the 3rd or 4th vaccinations shifted the peaks of anti-RBD antibody response curves significantly upward (by 28-fold [4–195] and 32-fold [4–234], respectively). However, there was no significant shift in the peak from the 3rd vaccination to the 4th vaccination (p = 0.64). Multivariable analysis showed that sulfasalazine increased the vaccine response (by 1.49-fold [1.13–1.97]), but abatacept or JAK inhibitor decreased the vaccine response (by 0.13-fold [0.04–0.43] and 0.44-fold [0.26–0.74], respectively). Age was associated with lower ln [anti-RBD] values (coefficient: − 0.03 [− 0.04 to − 0.02]). In conclusion, the anti-RBD response of RA patients peaked at 2 weeks after COVID-19 vaccination, and then decreased exponentially, with the maximum peak increase observed after the 3rd vaccination. The antibody response was affected by age and the medications used to treat RA.